Language, Identity and Conflict - Chríost, Diarmait (Routledge, 2004)
This innovative study of language and identity in recent and contemporary cases of ethnic conflict in Europe and Eurasia sets out a response to the limitations in the fields of linguistics and political science. Using examples of language policy and planning in conflict situations, it examines the functions of language as a marker of identity in ethnic conflict, and the extent to which language may be a causal factor in ethnic conflict.